A perspective on research ethics committees in the brazilian amazon - Carvalho de Moraes, Aparício; Nunes, Rui (Acta Bioethica, 2024)
This study presents the importance of the Research Ethics Committees (CEP) in the context of the Brazilian North Region, formed by the Amazon rainforest, which is occupied by traditional populations and those constituted by migratory currents. This study aims to analyze the bioethical implications arising from the activities of CEPs in the ethical evaluation of research projects and their essential role in protecting vulnerable populations. The authors seek to highlight the importance of ethics committees in the Amazon and their importance face the modern bioethical values that can contribute to the preservation of one of the most valuable and diverse environments on earth.